Physicochemical and sensory properties of mulberry products: Gümüşhane pestil and köme - YILDIZ, Oktay (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2013)
'Pestil' and 'kome', well known as traditional Turkish foods, are prepared from a mulberry, honey, walnut, hazelnut, and flour mixture. Although they have been produced for the last few decades on an industrial scale, the production methods and properties of the products are not standardized yet. Gumushane pestil and kome have been registered and attained Geographical Registration Certificates from the Turkish Patent Institute with their unique production methods and properties, among many similar products in the world markets. Thus, some biochemical, physical, and sensory properties of pestil and kome were investigated. In addition, the main raw material (mulberry) and semifinished product ('herle') were analyzed for some biochemical, physical, and rheological parameters. The characteristics of pestil and kome ranged from 9.78% to 20.06% for moisture content, 0.52% to 1.48% for crude fiber, 4.34% to 7.42% for protein, 41.04% to 62.54% for total sugar, and 37.52% to 56.23% for invert sugar, and the thickness, hydroxymethylfurfural (HMF), total phenolic content, and ferric ion reducing antioxidant power antioxidant activity ranged from 0.80 to 1.25 mm, 18.15 to 27.94 mg kg-1, 25 to 32 mg GAE per 100 g, and 81 to 92 mM TE g-1, respectively. Strong correlations between sugar contents and HMF content and between HMF and antioxidant activity (r > 0.5) were identified separately. The consistency index for herle was determined as 9.7-65.9 Pa s. Color parameters (L, a, and b) were read, and the difference in L between the product types was found to be statistically significant. Gumushane pestil and kome were found to be very different from other similar fruit leather products that are commercially available in terms of production method, composition, and biological and physical properties.
Keywords: 2. Zero hunger; 8. Economic growth